Pengaruh Penempatan dan Sudut Baffle Blocks Tipe Miring terhadap Redaman Energi, Panjang Loncatan Air dan Turbulensi Aliran pada Pelimpah Tipe Parabola dan Pelimpah Tipe Ogee - Sari, Lana Fatma, Gurawan Djati Wibowo, ST., M.Eng, Ir. A. Karim Fatchan, M.T (2016)
Water is one of the major necessities of live for living thing on this earth. Sometimes water availability with required is not same in space and time, so it is necessary for water utilization. One way to utilize of water is the weir. The effect of backwater caused by weir is the supercritic flow on downstream of weir, and occure hydrolic jump. Effect from this hydrolic jump still remains erode the river bottom in the downstream of weir. To reduce the scouring in downstream of stilling basin, so add baffle blocks in stilling basin. The purpose of this experiment is to verify the effectiveness of baffle blocks slanted type and baffle blocks with straight type in reduce energy flow, long hydrolic jump and turbulence. The experiment in this study conducted at the laboratory of hydaulics departement of Civil Engineering Faculty of Engineering, Muhammadiyah University of Surakarta. This experiment use a flume with a size of 30 cm × 60 cm × 1000 cm, a slope bottom of channel is 0,0058. This experiment use ogee and parabola spillway. Stilling basin use USBR-II type with add three variations of baffle blocks angle. The experiments was conducted with 5 series, each series is done 7 stages of running with 5 variations of discharge, so that the total running done as many as 14 running. At each discharge is done test of water long jump and energy loss. The result of experiment show some conclusions. First, the best baffle blocks arrangement to reduce energy flow is baffle blocks slanted type with an angle of 75° which is placed at the beginning of the stilling basin on parabola type (A75.P series). Second, the best baffle blocks position to reduce long hydrolic jump is baffle blocks slanted type with an angle of 75° which is placed at the beginning of the stilling basin on ogee type (A75.O series). Third, the best performance of shape and position of baffle blocks to reduce turbulence in the downsream of stilling basin is baffle blocks slanted type with an angle of 60° which is placed at the beginning of the stilling basin on parabola type (A60.P series).